Effects of Passion, Experience, and Cultural Politics on Classical Musicians’ Practice During the COVID-19 Pandemic - López-Íñiguez, Guadalupe; McPherson, Gary E.; Zarza Alzugaray, Francisco J.; Angel-Alvarado, Rolando (Frontiers in Psychology, 2022)
The widespread cancellation of cultural events during the early 2020 stages of the COVID-19 pandemic led professional performing musicians across the world to experience an increasing economic fragility that threatened their health and wellbeing. Within this “new normal”, developing countries have been at a higher risk due to their vulnerable health systems and cultural policies. Even in such difficult times, the music profession requires musicians to keep up their practicing routines, even if they have no professional commitments. This is because high level technical and expressive skills are crucial to sustaining a music career at a high performance level. However, it could be expected that not all musicians might have had the same engagement with music practice during lockdowns. In this study, we studied the experiences of 309 professional classical musicians based in European and Latin American countries with different levels of performing experience to examine their passionate (or lack thereof) engagement with music practice. Through the mixed methods combination of multigroup invariance and narrative analyses, we identified distinct profiles of musicians who displayed more harmonious or more obsessive passion orientations before and at the peak of the pandemic. We observed that musicians with higher levels of harmonious passion in particular were more capable of sustaining their practice at the peak of the pandemic, and that these musicians were mostly located in Latin America—a paradox, considering that cultural politics supporting the careers of professional performing musicians and entrepreneurial education in Latin America are lacking to a great extent, especially in comparison with the European context. We explain this in terms of the “forced” self-management embraced by musicians in Latin American countries who want to engage with music practice both before and during the COVID-19 pandemic even if the music profession does not generate enough revenue for them.